2012
DOI: 10.1111/j.1469-8986.2012.01354.x
|View full text |Cite
|
Sign up to set email alerts
|

Is “conflict adaptation” driven by conflict? Behavioral and EEG evidence for the underappreciated role of congruent trials

Abstract: Theories of cognitive control argue that response conflict in speeded performance tasks leads to adaptive changes, such that irrelevant information is better ignored on subsequent trials. This study tested whether trial-by-trial changes are driven primarily by conflict on incongruent trials or instead by congruent trials, in which irrelevant and relevant stimulus dimensions match. In a Stroop task including congruent, incongruent, and neutral trials, interference was greater following congruent compared to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 51 publications
6
48
1
Order By: Relevance
“…Therefore, disengagement of attention from the previous stimulus from a cognitive perspective occurs prior to presentation of the current stimulus, whereas disengagement of attention from the previous stimulus from an associative perspective occurs while the current stimulus is presented. In both accounts, degree and speed of disengagement from the previous trial contribute to the size of the SCE, with faster disengagement leading to smaller SCEs, a point supported in recent EEG studies showing disengagement between trials revealed by alpha power analyses (Compton et al, 2011, 2012). …”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Therefore, disengagement of attention from the previous stimulus from a cognitive perspective occurs prior to presentation of the current stimulus, whereas disengagement of attention from the previous stimulus from an associative perspective occurs while the current stimulus is presented. In both accounts, degree and speed of disengagement from the previous trial contribute to the size of the SCE, with faster disengagement leading to smaller SCEs, a point supported in recent EEG studies showing disengagement between trials revealed by alpha power analyses (Compton et al, 2011, 2012). …”
Section: Introductionmentioning
confidence: 63%
“…Note that in both of these accounts, the previous stimulus biases processing of the current stimulus, but some form of disengagement is required in order to avoid devoting all resources to elaborative processing of the no longer relevant stimulus. This interpretation is supported by EEG studies that show an initial increase in cortical activity immediately following a trial (reflecting adjustments in control), followed by a decrease in activity (reflecting disengagement of resources), and finally an increase in cortical activity immediately preceding the next stimulus (reflecting engagement; Compton et al, 2012). …”
Section: Introductionmentioning
confidence: 80%
“…Previous studies have shown that a high degree of conflict is associated with an increase in alpha activities (Min & Park, 2010), whereas a decrease in posterior alpha activities has been found in trials preceded by compatible stimuli in the Stroop task (Compton et al, 2012). These findings suggest that proactive control for the visual area is reflected in the increase in posterior alpha activities.…”
Section: Discussionmentioning
confidence: 88%
“…Several previous studies have shown that posterior alpha activity is enhanced on the ipsilateral side of the visual field attended to, while it is attenuated at the contralateral side (Freunberger et al, 2008;Rihs, Michel, & Thut, 2007;Rihs, Michel, & Thut, 2009;Sauseng et al, 2005;Thut, Nietzel, Brandt, & Pascual-Leone, 2006;Worden, Foxe, Wang, & Simpson, 2000). In terms of interference tasks, Compton, Huber, Levinson, and Zheutlin (2012) reported that alpha activity is reduced in trials preceded by compatible stimuli in the Stroop task, as compared with neutral stimuli, suggesting that reduced alpha activity is related to the enhancement of information processing about the irrelevant aspect. In addition, Min and Park (2010) examined prestimulus alpha activity in color and shape discrimination tasks, in which participants discriminated colors or shapes of objects, ignoring other aspects.…”
Section: Introductionmentioning
confidence: 94%
“…This version also might also predict a stronger effect of previous RT following incongruent trials (wherein conflict is relatively high) than following congruent trials (wherein conflict is relatively low), which we did not observe. However, yet another version of the notion that participants adapt to response conflict suggests that attention is widened in response to the absence of conflict on congruent trials, rather than narrowed in response to the presence of conflict on incongruent trials (Compton, Huber, Levinson, & Zheutlin, 2012;Lamers & Roelofs, 2011). This version might therefore better explain why previous-trial RT influences the congruency effect to a greater degree when the previous trial was congruent as compared to incongruent.…”
Section: Conflict Adaptationmentioning
confidence: 98%